PENGARUH VARIASI MERK BAHAN BAKAR, JENIS BUSI, DAN TEKANAN BAN TERHADAP PERFORMA MESIN SEPEDA MOTOR EMPAT LANGKAH - Wahyu Robby Cahyadi; Sudirman Rizki Ariyanto; Ata Syifa’ Nugraha; Rico Andhika Putra (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
This study aims to analyze the effect of variations in fuel brands, spark plug types, and tire pressure on four-stroke motorcycle engine performance. The independent variables tested include three variations of fuel brands (Pertamax, Shell Power, and AKR 92), spark plug types (standard, iridium, and platinum), and tire pressure (28 psi, 33 psi, and 38 psi). The experimental method was conducted on a Honda MegaPro PGM-FI motorcycle by measuring torque and power at various RPM using a chassis dynamometer test equipment. The results show that the sample 2 with combination of Shell-Super fuel brand, platinum spark plugs, and 33 psi tire pressure has a significant positive impact on engine performance, with higher torque and power as well as more consistent variations than other combinations. This research has important implications for motorcycle users, enabling them to optimize vehicle performance by choosing the right fuel, keeping spark plugs in good condition, and maintaining optimal tire pressure.